2020
DOI: 10.21518/2079-701x-2020-15-20-26
|View full text |Cite
|
Sign up to set email alerts
|

Differentiated approach to the choice of PPI in a patient with GERD in the practice of an outpatient (with a clinical case)

Abstract: In recent years, functional disorders of the gastrointestinal tract (GIT) are quite common. The most significant functional disorders are functional dyspepsia (FD), which is widespread in the population. In addition, in the clinical practice of outpatient doctors, the proportion of combined variants or overlap of several types of functional disorders or a combination of functional disorders with organic pathology has increased. So, according to systematic reviews, the combined course of gastroesophageal reflux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In one study, administration of a single dose of intravenous omeprazole to healthy subjects showed inhibition of the metabolism of diazepam and its derivatives. Omeprazole decreases clearance and prolongs the elimination halflife of diazepam and its derivatives [10]. In other words, Omeprazole can increase the level of diazepam in the blood, which means it increases the effectiveness of the diazepam.…”
Section: Assessment Of Drug-related Problemsmentioning
confidence: 99%
“…In one study, administration of a single dose of intravenous omeprazole to healthy subjects showed inhibition of the metabolism of diazepam and its derivatives. Omeprazole decreases clearance and prolongs the elimination halflife of diazepam and its derivatives [10]. In other words, Omeprazole can increase the level of diazepam in the blood, which means it increases the effectiveness of the diazepam.…”
Section: Assessment Of Drug-related Problemsmentioning
confidence: 99%